Kualitas Produk dan Digital Marketing Terhadap Loyalitas Pelanggan Melalui Kepuasan Pelanggan Pada Pengguna TOKOPEDIA - Andila, Nomy; Hayu, Rina Suthia (Universitas Islam Kadiri, 2023)
Along with the times and supported by the development of increasingly sophisticated technology, it can facilitate companies in marketing products or services on the internet, namely E-Commerce. Where E-Commerce companies are competing to offer the best deals to their customers. Customers who buy products have expectations that the products they buy must be of good quality and in accordance with what they want. This study aims to examine the mediating role of customer satisfaction on the effect of product quality and digital marketing on customer loyalty through customer satisfaction. In this study, the sample was 300 respondents who used Tokopedia. The results of this study found that product quality had no significant effect on customer satisfaction, digital marketing had a positive and significant effect on customer satisfaction, customer satisfaction had a positive and significant effect on customer loyalty, product quality had a significant effect on customer loyalty, digital marketing had a significant positive effect on customer loyalty, product quality had no significant effect on customer loyalty through customer satisfaction, digital marketing had a significant effect on customer loyalty through customer satisfaction. In future research to conduct studies or research that go deeper or even develop a concept or theory. can also conduct more in-depth research with the development of more comprehensive variables and more specific units of analysis related to product quality and digital marketing on loyalty through satisfaction. Future research can consider expanding the research object so that the results obtained are more accurate than this study.